2015
DOI: 10.17507/tpls.0507.19
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to Dynamic Assessment in Second Language Learning

Abstract: Abstract-The concept of the zone of the proximal development can contribute not only to the assessment, but also to the teaching within the second language learning environment. However, the unifying philosophy within sociocultural theory (SCT) in relation to language and thought has also merged the assessment and teaching procedures into the concept of Dynamic Assessment (DA). The process of DA lets the teacher/mediator permeate into both the actual and potential zones of the development. It teaches and asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
(28 reference statements)
0
3
0
1
Order By: Relevance
“…Finally, there is a worry that the DA's procedure may challenge the reliability and fairness of the test [23]. In addition, it had been argued that these problems refer only to the question of where the priority should be placed [25][26][27]. In exclusive way, Murphy believed that DA supporters emphasize its focus on all individual itself rather than the the scores of the test [28].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, there is a worry that the DA's procedure may challenge the reliability and fairness of the test [23]. In addition, it had been argued that these problems refer only to the question of where the priority should be placed [25][26][27]. In exclusive way, Murphy believed that DA supporters emphasize its focus on all individual itself rather than the the scores of the test [28].…”
Section: Introductionmentioning
confidence: 99%
“…Proses penilaian dynamic assessment berbeda dengan penilaian sumatif, yaitu penilaian dynamic assessment lebih menekankan pada proses peningkatan keterampilan dalam menyelesaikan permasalahan dan memberikan kesempatan pada pendidik untuk melihat perkembangan pembelajar melakukan proses mediasi atau pemberian umpan balik (Mehri & Amerian, 2015;Mohamadi, 2018). Hal ini sesuai dengan kriteria instrumen yang dikembangkan, yaitu menekankan pada membantu proses kontruksi konsep klasifikasi tumbuhan dengan benar.…”
Section: Unidimensionalitas Butir Soalunclassified
“…Similarly, Miri et al ( 2017) have shown in their study which is concerned with the difference between dynamic assessment and non-dynamic assessment that both types can be successful to assist how much learners understand the definite and indefinite articles in English; nevertheless, concurrent dynamic assessment is of a great value since it could better engage learners both verbally and bodily. Furthermore, Amerian and Mehri (2015) have investigated the impact of DA on gaining control over the past tense. They have found that students who have received interactionalist dynamic assessment show an apparent advancement at the end of the instructional sessions as well as obvious management to use the past tense in new situations.…”
Section: Dynamic Assessment Vs Non-dynamic Assessmentmentioning
confidence: 99%